The Impact Of The Blockade And Politics On Health And Social Welfare In Palestine - Fitria Risdayani; Karina Mancanagara; Nurul Anisa (Eduvest - Journal of Universal Studies, 2024)
The political conflict between Israel and Palestine has created a difficult situation for the Palestinian population, with a blockade imposed by Israel and persistent political tensions. The impact of the blockade and politics on the health and social well-being of the Palestinian population requires in-depth research to fully understand its implications. This research aims to analyze the impact of the blockade and politics on physical and mental health, access to health services, and the social welfare of Palestinian society. This research uses the Systematic Literature Review (SLR) method to collect and analyze data from various related literature sources. Data was analyzed comprehensively to understand the impact of the blockade and politics on health and social well-being in Palestine. The results show that the blockade imposed by Israel has caused a severe health crisis, with increased risks of infectious diseases, shortages of medical equipment, and limited access to health services. In addition, political conflict has also caused an increase in mental disorders among the Palestinian population, as well as disturbing social instability.